Characterization of MEA degradation for an open air cathode PEM fuel cell - Silva, R. A. (2013)
As fuel cell technology matures and time scale to commercialization decreases, the need for a more comprehensive knowledge of materials’ aging mechanisms is essential to attain specified lifetime requirements for applications. In this work, the membrane electrode assembly (MEA) degradation of an eight-cell PEM low power stack was evaluated, during and after fuel cell aging in specified testing conditions of load-cycling that may compromise the durability of the catalyst. The stack degradation analysis comprised observation of catalytic layers, morphology and composition. Examination of the MEAs cross sections, in a joint SEM and TEM study, revealed thickness variation of catalytic layer (up to 47% for the cathode layers), and cracking, delamination, and catalyst migration were observed even though catalyst sintering and consequent loss of electrochemical active area seem to be predominant together with F loss from the ionomer used as binder in the catalytic layers.